Analisis Etnomatematika Pada Kue Tradisional Bugis Dan Penerapannya Dalam Pembelajaran Geometri - Nurdin, Hasnawati; Nur, Fitriani; Yuliany, Nur (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
This research aims to analyze the ethnomathematics concepts contained in traditional Bugis cakes and their application in geometry learning at school. The background to this research is the need for a mathematics learning approach that integrates local culture to increase students' understanding while preserving cultural heritage. The research method used is descriptive exploratory with a qualitative approach, involving observation, interviews and documentation. The research results show that traditional Bugis cakes such as doko-doko utti, bolu cukke, cangkuning, onnde-onde, and nennu-nennu have geometric shapes related to geometric concepts, such as squares, balls, pyramids, and tubes. The application of these concepts helps students understand mathematics through concrete objects that are close to everyday life. This research contributes to geometry learning by introducing an innovative approach based on local culture that is relevant and interesting for students, while preserving tradition through education. Keywords : Ethnomathematics, Geometry, Traditional cakes, Education.